Doctoral writing groups for the advancement of dissertation and publication writing - Colombo, Laura Marina (2024)
In writing groups (WGs), participants exchange drafts so that their partners’ feedback can be used to improve writing. These groups accompany participants while they face authentic dissertation or publication writing projects, are linked to situated and real demands, and promote participants’ engagement. Nevertheless, this type of pedagogical initiative continues to be uncommon, especially in Latin America. This qualitative exploratory study analyses participants’ perspectives about the benefits and drawbacks found in joining doctoral WGs in the Humanities and Social Sciences. It focuses on three separate sets of doctoral writing groups implemented and facilitated within the last eight years in Argentina. Despite some drawbacks, participants considered these groups as valuable not only for the advancement of dissertation and publication writing, but also as horizontal spaces to develop as scholarly writers. Higher education institutions worldwide could benefit from similar pedagogical initiatives to enhance and promote research writing at the graduate level.